2005
DOI: 10.1626/pps.8.525
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Vegetative Growth Response to Soil Flooding between Common and Tartary Buckwheat

Abstract: Abbreviations : DPL, dry-matter partitioning ratio to leaf; DW, dry weight; FW, fresh weight; GR L , leaf growth rate; LA L, leaf area per leaf; LN, number of leaf; MLA, mean leaf area; NAR, net assimilation rate; PGR, plant growth rate; RGR, relative growth rate; RWC, relative water content; SLA, specifi c leaf area; TW, turgid weight. and 45% of the control, respectively, in Nepal. The excess moisture stress had no effect on the net assimilation rate (NAR) in Shinano No.1, but lowered the NAR to 68% of that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…(Dias-Filho and, barley (Hordeum vulgare) (Pang et al, 2004), de Carvalho, 2000;Dias-filho, 2002) or maize (Zea mays L.) buckwheat (Fagopyrum sp.) (Matsuura et al, 2005) and (Lizaso and Ritchie, 1997). Our results show that cv.…”
Section: Onwards a Higher Height Reduction With Longersupporting
confidence: 50%
“…(Dias-Filho and, barley (Hordeum vulgare) (Pang et al, 2004), de Carvalho, 2000;Dias-filho, 2002) or maize (Zea mays L.) buckwheat (Fagopyrum sp.) (Matsuura et al, 2005) and (Lizaso and Ritchie, 1997). Our results show that cv.…”
Section: Onwards a Higher Height Reduction With Longersupporting
confidence: 50%
“…The ability to sustain leaf growth under prolonged flooding conditions (extended from 30 DAE) may be facilitated by the active nodal and lateral root growth and aerenchyma formation in roots, plant's axes and stalk base. The development of adventitious or nodal roots has been previously reported to support leaf growth of waterlogging tolerant soybean (Henshaw et al, 2007) and buckwheat (Matsuura et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…In water-loving species, intercellular gas-filled spaces that often extend from the shoots to near the root tips could enhance transport of oxygen, carbon dioxide and ethylene between plant parts above water and submerged tissues (Armstrong, 1979;Laan et al, 1990). The ability of plants to produce adventitious roots and nodal roots and aerenchyma formation in roots are important characters for flooding-tolerant crops (Orchard & Jessop, 1985;McDonald et al, 2001McDonald et al, , 2002Zaidi et al, 2003Zaidi et al, , 2004Matsuura et al, 2005;Mano et al, 2006;Henshaw et al, 2007;Kubo et al, 2007). Glaz et al (2004) also reported aerenchyma formation in stalks that supports internal gas spaces resulting in enhanced cane yield and sucrose yield in sugarcane.…”
Section: Introductionmentioning
confidence: 99%
“…It is amusing that the genotype BINAmasur1 showed drastic reduction in number of leaves during flooding compared to control, but this did not appear as constant declining in number of leaves as observed in other genotypes. Matsuura et al (2005) found that the number of leaves in buckwheat plant was significantly reduced by waterlogging stress to 60% of the control. The number of leaves per plant during flooding and after termination of flooding also reduced significantly in mungbean plant at vegetative stage (Ahmed et al, 2002).…”
Section: Number Of Leavesmentioning
confidence: 92%